Biomechanics - Principles and Applications (CRC Press, 2008)
Drawn from the third edition of the widely acclaimed The Biomedical Engineering Handbook, Biomechanics is a comprehensive presentation of the current principles and applications of biomechanics integrating both systems and subsystems models. Presenting substantial updates and revisions and a new chapter on current methods and strategies for modeling cellular mechanics, the book covers musculoskeletal mechanics including hard- and soft tissue and joint mechanics, biofluid mechanics and circulatory dynamics, the functioning of the ear, and the performance characteristics of the human body during exercise and exertion. The book includes more than 140 illustrations, 60 tables, and a variety of useful equations to assist in modeling biomechanical behaviors.